Bridging the Gap – Physical Health Management by Mental Health Nurses in Pendleview: A Quality Improvement Project - Faisal Alam; Celina Mitala; Aarthi Krishnan; Ushbah Ali; Abdalla Salih (BJPsych Open)
Aims: To reinforce nurses’ initial physical health management knowledge on Darwen and Calder wards at Pendleview unit (LSCFT). This quality improvement project attempted to bridge the gap (of physical health knowledge) amongst nursing staff by providing a short teaching course of 3 topics to mental health nurses on Darwen and Calder ward at Pendleview mental health unit, Royal Blackburn Hospital.